Impact of Aquafitness Training on Physical Condition of Early Adulthood Women - Vitalii Kashuba; Olena Andrieieva; Anna Hakman; Igor Grygus; Olga Smoleńska; Małgorzata Ostrowska; Marek Napierała; Magdalena Hagner-Derengowska; Radosław Muszkieta; Walery Zukow (OVS LLC, 2021)
Background. The physical benefits of fitness for middle-aged women are well-known. Unlike the usual training sessions, aquafitness occupies a special place among the types of health-related exercise training. Its health-enhancing effect results from the activation of the body's functional systems, the gravitational unloading of the musculoskeletal system, high energy expenditures, and overall body hardening effect.  The objective of this study was to evaluate the health-enhancing effects of an aquafitness program on the functional indicators and physical fitness of early adulthood women.  Materials and methods. Theoretical analysis and generalization of scientific and methodological literature, anthropometric techniques, pedagogical methods, and methods of mathematical statistics were used. The functional status of the body was assessed with the indices characterizing the function of the cardiorespiratory system, which are commonly used. The study was conducted at the Sport Life fitness club, Chernivtsi. The study involved 48 women aged 21-31 with an average age of 26.3 years. The subjects took part in a six-month aquafitness program consisting of 60-min sessions, three times a week. The program was developed by the authors and included aquatic stretching, body shaping and bodybuilding exercise, aquadance, aquatic gymnastics, and aqua tae-bo.  Results. After participation in the exercise program: vital capacity increased from 45.96±4.69 to 48.88±0.68; strength index increased from 35.80±1.07 to 43.26±0.71; Robinson's index increased from 85.72±12.34 to 89.63±10.11; Shtange test increased from 30.28±10.32 to 37.78±12.34; Hench test changed from 16.48±4.24 to 25.19±4.58; Kerdo index decreased from 5.23±0.74 to 0.88±0.38; and Rufier's test decreased from 12.21±4.26 to 8.03±2.14. The assessment of somatic health of the women showed a significant improvement (p<0.05). Positive changes in the autonomic system were detected. Conclusion. The developed aquafitness program can be an effective tool for health improvement and body weight management in early adulthood women.